Innovation of Information Technology-Based Tourism Services During the COVID-19 Pandemic - Camalia, Farhah Millati; Yuniningsih, Tri (KnE Social Sciences, 2022)
The Covid-19 pandemic has affected various sectors, including the tourism sector. The province of Yogyakarta has been impacted, particularly its tourism sector. Yogyakarta’s tourism sector has therefore had to explore innovations during the Covid-19 pandemic, including the innovation of information technology-based tourism services. The research objectives were to identify the tourism services innovations implemented by the Yogyakarta Government during the Covid-19 pandemic and to determine the obstacles faced in implementing these innovations. The research used descriptive qualitative methods and data were collected through document analysis and observations. The results showed that Yogyakarta made an application named Visiting Jogja as part of its tourism efforts during the Covid-19 pandemic. The obstacles in implementing this Visiting Jogja application were: most people did not understand the application, some people still had limited access to android or IOS smartphones, and there was unstable internet connection in many areas of Yogyakarta. Based on the research, it can be concluded that the implementation of the Visiting Jogja tourism service innovation was not run well, since most people still do not use this application when they travel to Jogja and some Yogyakarta tourism destinations are still not strictly implementing the application. Keywords: public services innovation, tourism, Covid-19 pandemic